PENGARUH PENDIDIKAN KEWIRAUSAHAAN TERHADAP NIAT BERWIRAUSAHA SISWA SMK NEGERI 1 PEDAN TAHUN 2013 - Wahyono, Budi; M.Stats, Siswandari; Santosa, Djoko (Jurnal Pendidikan Insan Mandiri, 2015)
The purposes of this study are to figure out: 1) the difference student?s entrepreneurial intention between class with entrepreneurship practice (experimental class) and class without entrepreneurship practice (control class), 2) the difference student?s entrepreneurial intention before and after the instructional practices of entrepreneurship and 3) the impact of entrepreneurship education on student?s entrepreneurial intention based on Theory of Planned Behavior.This research used quantitative approach with quasi-experimental methods. The research populations consisted of all the student of grade XI of SMK Negeri 1 Pedan academic year 2012/2013. The research sample were all the student of grade XI of Accounting, which taken by cluster random sampling. Questionnaire and documentation used to collect the data. Data analysis techniques were t-test and path analysis.The results of this study are as follows: 1) there is a significant difference between students? entrepreneurial intention the experimental class and control class, 2) there is a significant difference in student?s entrepreneurial intention before and after the instructional practices of entrepreneurship, 3) entrepreneurship education significantly influence the student?s entrepreneurial intention based on the Theory of Planned Behavior, 4) directly, components of the Theory of Planned Behavior give effect to the students? entrepreneurial intention by 53%, and 5) the overall effective contribution of the model is 79.7%, that result is the impact of entrepreneurship education components based on the Theory of Planned Behavior on students? entrepreneurial intention directly and indirectly.Keywords: Entrepreneurship Education, Theory of Planned Behavior, Entrepreneurial Intention